Initial Coefficient Estimates and Fekete–Szegö Inequalities for New Families of Bi-Univalent Functions Governed by (p − q)-Wanas Operator - Abbas Kareem Wanas (MDPI AG, 2021)
The motivation of the present article is to define the <semantics>(p−q)</semantics>-Wanas operator in geometric function theory by the symmetric nature of quantum calculus. We also initiate and explore certain new families of holormorphic and bi-univalent functions <semantics>AE(λ,σ,δ,s,t,p,q;ϑ)</semantics> and <semantics>SE(μ,γ,σ,δ,s,t,p,q;ϑ)</semantics> which are defined in the unit disk U associated with the <semantics>(p−q)</semantics>-Wanas operator. The upper bounds for the initial Taylor–Maclaurin coefficients and Fekete–Szegö-type inequalities for the functions in these families are obtained. Furthermore, several consequences of our results are pointed out based on the various special choices of the involved parameters.